A Comprehensive Overview of US-FDA-Approved Anticancer Drugs and Biologics in 2023: An Observational Study - Ajay Kumar Shukla; Saurav Misra (Journal of Pharmacy and Bioallied Sciences)
Background: The United States Food and Drug Administration (US FDA) is responsible for ensuring public health by conducting a comprehensive assessment and approval of pharmaceuticals, medical devices, and food products. The federal agency conducts a thorough evaluation of drug safety and efficacy before granting market approval. Materials and Methods: This retrospective study aimed to analyze all new drug approvals that took place during the 2023 study period using an observational, record-based approach. To gather data on drug approvals by the US FDA, we relied on the FDA database website. We also conducted a literature search on electronic databases like PubMed, ClinicalTrials.gov, and the Cochrane Database to gather comprehensive drug-related information. Results: In the calendar year (CY) 2023, a total of 55 drugs were approved by the US-FDA, out of which 23 drugs (42%) were given orphan drug designation, and 12 drugs (22%) were approved in the first-in-class category during this period. The US-FDA granted 7 breakthrough approvals, 22 priority approvals, 18 fast track approvals, 2 qualified infectious disease product designations, and 4 accelerated approvals in CY 2023. There were 16 drugs (29%) that were approved for cancer in 2023 by the US FDA. Out of the 16 drugs, 6 belonged to the tyrosine kinase class, 6 were monoclonal antibodies, and 1 each was a gamma secretase inhibitor and an estrogen receptor antagonist. During CY 2023, 16 (29%) biological drugs were approved, which included monoclonal antibodies, (n = 12), enzymes derivatives (n = 3), and hormones derivatives (n = 1). Conclusion: Notable advancements in the drug development market were witnessed between 2015 and 2022, and 2023 was no different. The total number of novel drugs approved was significantly higher than the previous year. Expedited approval of anticancer drugs and biologics is seen as a recent trend in drug development.